1988
DOI: 10.1007/bf00735871
|View full text |Cite
|
Sign up to set email alerts
|

An open label trial of raclopride in acute schizophrenia. Confirmation of D2-dopamine receptor occupancy by PET

Abstract: Raclopride, a highly selective D2-dopamine receptor antagonist, was administered in doses up to 4 mg b.i.d. to ten schizophrenic patients in an open label non-comparative study lasting 4 weeks. Safety, tolerability, potential antipsychotic effect, prolactin response and drug effect on plasma homovanillic acid were evaluated. Central D2-dopamine receptor occupancy was determined by positron emission tomography (PET). No major deviations were found in biochemical and physiological safety parameters. Raclopride w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 23 publications
3
38
0
1
Order By: Relevance
“…The results for the selective D 2 antagonist raclopride show an association between increased EMG activity and D 2 receptor occupancy which is similar to that reported for raclopride from PET studies (Farde et al 1988; Nördström et al 1993). PET studies have shown the level of striatal D 2 occupancy associated with EPS to be 70%-89% for a number of typical antipsychotic drugs (Farde and Nördström 1992a;Farde et al 1992b Farde et al , 1992cNyberg et al 1995).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results for the selective D 2 antagonist raclopride show an association between increased EMG activity and D 2 receptor occupancy which is similar to that reported for raclopride from PET studies (Farde et al 1988; Nördström et al 1993). PET studies have shown the level of striatal D 2 occupancy associated with EPS to be 70%-89% for a number of typical antipsychotic drugs (Farde and Nördström 1992a;Farde et al 1992b Farde et al , 1992cNyberg et al 1995).…”
Section: Discussionsupporting
confidence: 84%
“…It thus complements the findings from PET studies in humans (Farde and Nördström 1992a;Farde et al 1992b Farde et al , 1992c and occupancy studies in experimental animals Schotte et al 1993;Sumiyoshi et al 1993Sumiyoshi et al , 1995. The current findings show that there are dose-related increases in EMG activity which are associated with dose-related increases in D 2 dopamine receptor occupancy in the striatum and substantia nigra.The results for the selective D 2 antagonist raclopride show an association between increased EMG activity and D 2 receptor occupancy which is similar to that reported for raclopride from PET studies (Farde et al 1988; Nördström et al 1993). PET studies have shown the level of striatal D 2 occupancy associated with EPS to be 70%-89% for a number of typical antipsychotic drugs (Farde and Nördström 1992a;Farde et al 1992b Farde et al , 1992cNyberg et al 1995).…”
supporting
confidence: 84%
“…Clinical equivalence of drugs is particularly important to this experiment, because it is at these relative doses that the drugs have equivalent antipsychotic efficacy and are used clinically. The clinically equivalent dose of raclopride in this experiment would have been approximately 2.0mg/kg/day (Farde, 1988); but, a dose of 10 mg/kg/day raclopride was selected for other experimental reasons. Clozapine, being approximately 15-20 times less potent than haloperidol in treating psychosis, was administered at 25 mg/kg/day (Kane et al, 1988).…”
Section: Drug Administration and Dose Rationalementioning
confidence: 99%
“…Studies conducted using sulpiride report either no change in striatal binding with advancing age (Memo et al, 1980) or a more subtle, subregion-specific age-related decline in caudate D2 binding (Morelli et al, 1990). These apparent differences in raclopride and sulpiride binding may in fact represent metabolic differences between in vivo and in vitro studies, as raclopride is the superior ligand for PET studies due to its greater bioavailability and brain penetration (Farde et al, 1988); considerations that are not relevant to postmortem work.…”
Section: Dat and D1 Receptor Binding In The Dorsal Striatum Decreasesmentioning
confidence: 99%